(untitled) (Journal of Information Technology and Digital World, 2023)
The rapid growth of electric vehicles (EVs) has spurred the need for a robust and secure charging infrastructure to ensure the future of mobility. This comprehensive study explores the critical topic of securing electric vehicle charging infrastructure, focusing on the protection of the vital component of the EV ecosystem. The study begins by providing an overview of the different types of EV charging infrastructure and the current state of deployment. It then examines the inherent challenges and vulnerabilities associated with EV charging infrastructure security, encompassing both physical threats, such as vandalism and theft, as well as cybersecurity threats, such as unauthorized access and data breaches. Existing security measures, including physical site design considerations and cybersecurity protocols, are reviewed, along with industry standards and regulations that provide guidance in this domain. The emerging technologies and strategies, such as blockchain, artificial intelligence, and secure communication protocols, that can enhance the protection of EV charging infrastructure are also explored in the study. Furthermore, it analyses relevant case studies illustrating real-world attacks on charging infrastructure, successful deployment stories, and the valuable lessons learned from these experiences. Finally, the paper outlines future directions and recommendations, including research needs, policy considerations, and stakeholder collaboration, aimed at establishing a secure and resilient EV charging ecosystem. By comprehensively addressing the security challenges surrounding EV charging infrastructure, the study aims to contribute to the advancement of effective measures and strategies to safeguard the future of mobility in an increasingly electrified world.